PELATIHAN MANAJEMEN USAHA DAN SISTEM INFORMASI AKUNTANSI PADA UMKM CLOTHING DI SURAKARTA - Sohidin Sohidin; Endri Kristanto (Department of Economics Education, Universitas Sebelas Maret, 2017)
In line with the development of lifestyles and social dynamics, there is now a growing range of creative economic ventures. One of the fastest growing creative economy business in Surakarta is Small and Medium Enterprises (SMEs) for Clothing. This SMEs manufactures fashion products with a customized model of market trends. However, not many Clothing SMEs are able to survive and operate long enough, this due to errors in financial management and limited capital. This activity aims to give training in accounting information system on SMEs Clothing in Surakarta. Information system that trained is a system that suits with the needs of SMEs. Using questionnaires for evaluating the success of the training, the results show that the trained system that assessed by the SMEs are easy to use and usefulness in preparing the financial statements.